Seamless Rate Adaptation for Wireless Networking - Cui, Hao; Luo, Chong; Tan, Kun; Wu, Feng; Chen, Chang Wen (Proceedings of ACM MSWiM'11, 2011)
This paper aims at designing a Seamless Rate Adaptation for wireless networking which achieves smooth rate adjustment in a broad dynamic range of channel conditions. Conventional rate adaptation can only achieve a stair-case rate adjustment. Even when combining with hybrid ARQ, it suffers from an irreconcilable conflict between throughput and dynamic range. We tackle this problem from a new perspective by relying on modulation, instead of channel coding, for rate adaptation. We propose rate compatible modulation (RCM), in which modulation signals are incrementally generated from information bits through weighted mapping. Rate adaptation is achieved through varying the number of modulated signals. As more signals are transmitted, information bits gradually accumulate energy. The weights in bit-to-symbol mapping are delicately designed to ensure fine-grained energy accumulation so that smoothness and efficiency can both be achieved. We design and implement a rate adaptation system, called SRA and evaluate its performance through a software radio testbed. Results show that, under highly dynamic channel conditions, SRA achieves over 80% throughput gain over 802.11a adaptive modulation and coding, and achieves 28.8% and 43.8% gain over HARQ systems implemented with Turbo code and Raptor code. We believe that the concept of rate compatible modulation opens up a fresh research avenue toward the wireless rate adaptation problem.